Succession Planning Strategies and Employee Performance of Selected Deposit Money Banks in Lagos State, Nigeria: The Moderating Effect of Educational Qualification - Egwakhe , A J; Akinlabi , B H; Magaji , N; Ojuolape , S A (European Journal of Human Resource, 2022)
Purpose: Employees' performance was investigated along succession planning strategies and roles played by educational qualifications. This study examined the relationship between succession planning strategies and employee performance of selected money banks in Lagos State, Nigeria with the moderating effect of educational qualification. Methodology: The study adopted survey research design. The target population for this study comprised twenty thousand and five (25005) employees of five selected money banks in Lagos State, Nigeria. A sample size of 760 was chosen to stand in for the entire population of the study. Stratified and simple random sampling techniques were used to determine the sample size. Hierarchical Multiple Regression technique was used to test the study's hypothesis. Findings: Findings indicated that succession planning strategies have significant effect on employees' performance among selected deposit money banks in Lagos State, Nigeria. Findings further revealed that educational qualification significantly moderated the relationship between succession planning strategies and employee performance among deposit money banks in Lagos State, Nigeria. Recommendation: The study recommends continuous learning and capacity building to ensure better fit and qualified persons occupy position to succession planning.